Given that f ( x ) = x 2 − 1 x 2 , compute
5 1 × [ f ( 5 0 ) × f ( 4 9 ) × ⋯ × f ( 3 ) × f ( 2 ) ] .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Here's a way to formally write the solution using product notation (which involves the idea of your solution):
f ( x ) = x 2 − 1 x 2 = x − 1 x ⋅ x + 1 x
The expression (call it P ) given to us is:
P = 5 1 ⋅ x = 2 ∏ 5 0 f ( x ) = 5 1 ⋅ x = 2 ∏ 5 0 ( x − 1 x ⋅ x + 1 x ) 5 1 P = ⎝ ⎜ ⎜ ⎜ ⎜ ⎜ ⎛ ( x = 1 ∏ 4 9 x ) ⋅ ( x = 3 ∏ 5 1 x ) ( x = 2 ∏ 5 0 x ) 2 ⎠ ⎟ ⎟ ⎟ ⎟ ⎟ ⎞ = 5 1 2 × 5 0 ⟹ 5 1 P = 5 1 1 0 0 ⟹ P = 1 0 0
A few notations used:
Problem Loading...
Note Loading...
Set Loading...
We start with a smaller group of Numbers. f(50) * f(49) * f(48)
Simplifying, we get.... (We factored the denominator of f(x))
( 5 0 + 1 ) ( 5 0 − 1 ) 5 0 2 ∗ ( 4 9 + 1 ) ( 4 9 − 1 ) 4 9 2 ∗ ( 4 8 + 1 ) ( 4 8 − 1 ) 4 8 2
We can see that we can cancel some terms. After cancelling we get....
5 1 ∗ 4 7 5 0 ∗ 4 8
WE see that on the top we get the first number and the last number multiplied together, while on the bottom we get the first number + 1 and the last number -1.
Using the generalization we get...
5 1 ∗ 1 5 0 ∗ 2
We have to multiply the overall expression by 51, so we can simplify to 100. That is the answer.
(If you have any question please ask below, I shortened my explanation because I do not know how to use Latex and it was getting hard to write the solution using the new Latex Method that I just learned (kind of))